Numerical analysis of ventilated windows’ thermal behaviour under summer condition - Najaf Khosravi, Shiva; Mahdavi, Ardeshir (CLIMA 2022 conference, 2022)
Efforts to develop advanced building envelope components have pursued, among other things, ventilated window constructions. To properly configure ventilated windows, both the operation mode and the climatic context must be taken into consideration. In the framework of a previous research project, an instance of a ventilated window (outdoor air curtain mode) was implemented in a testbed and was subjected to experimental studies under summer conditions. In the present contribution, we numerically evaluate the thermal behavior of this system via computational fluid dynamic (CFD) simulation. Specifically, we compared simulation results with measurement data to evaluate the accuracy of the simulation model. Thereby, the main objective was to explore the fidelity of the CFD model and its potential for supporting the design of ventilated windows. To this end, the utility of the CFD was demonstrated in terms the optimization of the design of a ventilation window (exhaust and outdoor curtain mode). In the course of this study, we numerically analyzed the thermal behavior of the two modes of ventilation window operation (exhaust and outdoor curtain mode) under summer conditions. The results of the CFD-based investigation suggest that the application of low-emissivity glazing as the exterior glass pane can improve the cooling effect in both cases. In addition, the exhaust mode of the ventilated window shows a better performance under summer boundary conditions.